Learning Bryophyta: Improving students’ scientific literacy through problem-based learning - Vitri Anugrah Nainggolan; Risya Pramana Situmorang; Susanti Pudji Hastuti (JPBI (Jurnal Pendidikan Biologi Indonesia), 2021)
Regarding 21st-century learning, scientific literacy is an important competency which must be owned by students. Nevertheless, scientific literacy of Indonesian students has been recognized in low level. This study aimed to describe students’ scientific literacy in Bryophyta topic using problem-based learning. This Classroom Action Research (CAR) used the Kemis & Mc.Taggart research design. This study involved 30 students of X graders in Kristen Satya Wacana Senior High School. Students' scientific literacy was measured using a test which comprised of 15 MCQs and 5 essay questions. The data obtained was analyzed using N-gain score. The results indicated that students' scientific literacy was improved from cycle 1 (45.20) to cycle 2 (65.59) as they learnt about Bryophyta. The use of PBL in learning Bryophyta accommodates students' activities to promote their scientific literacy. Scientific activities in PBL strongly support the development of students' scientific literacy.